Pembuatan Dan Instalasi Penerangan Jalan Umum (PJU) Artistik Berbasis Panel Surya Di RT 20 Seladu, Desa Parit Raja, Sambas - Pande Putu Agus Santoso; Iklas Sanubary; Iman Syahrizal; Irma Fahrizal Butsi Ningsih; Amien Rais; Herry Siswanto; Hafizan Zuhri; Basha Ayumi (AMMA : Jurnal Pengabdian Masyarakat, 2025)
The Community Service Program aims to install an artistic Public Street Lighting (PSL) based on solar panels in RT 20 Seladu, Parit Raja Village, Sambas. The problem that based this program was the people of RT 20 Seladu difficult to do activities at night because there were none lighting on the street. On the other hand, this region has abundant solar energy potential, because it was located near to the equator. This program uses the PALS method which consists of three stages: awareness, capacitation, and monitoring. The awareness stage was carried out to provide an understanding of the use of renewable energy for street lighting. The capacitance stage focuses on the manufacturing and installation of PSL based on solar panel. At the monitoring stage, inspection and maintenance activities were carried out for PSL units based on solar panels that have been installed. The result of the activity was that four PSL based on solar panel have been successfully established. These four PSL function well. PSL was capable of turning on automatically at night and turning off automatically when the solar panel was exposed by sunlight. During the day PSL was able to convert sunlight into electricity and store it on the battery. During the monitoring process, it was known that 2 PSLs experienced a power outage. After being inspected, it turned out that the lights were broken. Repairs were made by lowering the PSL light pole and replacing the light bulb while cleaning the surface of solar panel. This PSL was made with a lock down system, where the light pole and the foundation were connected by bolts. This causes the maintenance and repair process to be carried out efficiently.